A Retrospective Chart Review Examining Gabapentin's Potential Neuroprotective Effects in Peripheral Nerve Blocks. Issue 4 (22nd October 2020) - Shuster, David M.; Brower, Jacob; Cheney, Nicholas A.; Clark, Brian C.
Category: Other Introduction/Purpose: Regional anesthesia is routinely used in association with outpatient surgical procedures to mitigate postoperative pain. This has been associated with better surgical outcomes and decreased post-surgical opioid consumption. Administration of a nerve block; however, can lead to complications. These complications are typically due to nerve damage caused by the injection and leading to lasting neurologic symptoms unrelated to the surgical procedure itself. Although nerve block complications are rare and temporary, lasting complications can be debilitating. Based upon a few total knee arthroplasty studies this study theorized that Gabapentin could be used as a neuroprotectant thereby decreasing the rates of lasting complications from peripheral nerve blocks. This study compares the number of nerve block complications with and without the use of Gabapentin peri/post operatively. Methods: This study was completed through retrospective chart analysis of the senior author's patients from January 2019 to September 2019. Charts of patients that received a preoperative nerve block were used to calculate rates of lasting complications. The rate of complications in this subset of patients was compared to the group of patients who did not receive this medication pre and post operatively from an earlier study. Results: Nerve block complication rates when administering 600mg of gabapentin 1-hour pre-surgery along with 100 mg of gabapentin three times daily for three days post-surgery, was 7.69% (N = 78; P=0.4261). However, there was an insufficient number of study participants to make a definitive conclusion. Conclusion: Administration of pre and post-operative gabapentin does not decrease nerve block complication rates when compared to no pre and post-operative gabapentin to a statistically significant amount. This was largely due to limited sample size, which was a major limitation of this study. A previous study was done with the same physician and the same patient population. In this study they found a 10.1% complication rate, seen in the evaluation of 855 patients charts. Due to a discrepancy in sample size, a conclusion cannot be made but further research is necessary to understand gabapentin's potential neuroprotective effects in nerve blocks.